Uma trajetória hipotética de aprendizagem sobre funções logarítmicas - Lima, Patrick Oliveira de (2009)
This work has as objective, contribute to the reflection about an important moment in the process of curriculum implementation, in other words, the one which is developed inside of the classroom, analyzing how its plan can be done and where is the teacher related to this process. It has as a theoretician recital the Simon s works about hypothetical trajectories of learning (HTL), expression that he uses to refer to the prognostic from teacher to teach and he uses this expression to show the way that will make the learning process possible. It is a research of qualitative features, because the concern with the process is a constant during the research: the main interest of investigation is the one to evidence how is the planning process and the education accomplishment done, in a growing perspective of learning. The research counts on the contribution of two Math teachers of a public school from São Paulo and their performance among 80 students from high school. In this research, we developed a HTL project about logarithmic functions, searching to involve contextualized situations, interdisciplinary situations and made of activities of problems resolution, involving applications on daily situations, in another knowledge areas and main for the mathematics area. With our work, we intend to contribute to the professional development of the teachers in a consistent way that is intended to be practiced in class, by an articulation strategy between theory, teaching practice and research